Manejo y clasificación según Wagner modificada en pacientes con pié diabéticos del Hospital Regional Isidro Ayora de Loja durante el periodo marzo-octubre 2014 - Atariguana Zhingre, Nadia Tatiana (2015)
The present research is a descriptive study, cross-sectional applied to patients that arrived to the clinic Regional Hospital Isidro Ayora, considering the inclusion and exclusion criteria, for which clinic history was used and a survey previously prepared, to collect the data; found that 55% of patients with diabetic foot were men, the most affected group consists of 46 to 65 years represents 56% of cases and had more than 10 years of evolution of their illness; other risk factors were identify, poor metabolic control was the most common modifiable factor with 62%, shown by laboratory data and the unchangeable factor is the abnormal foot structure; the most predominant triggering event was penetrating puncture injury with 36%; depending on the severity of the injury, the classification of Wagner was use where the prevalence of grades III, IV and V with 47% was determinate; IIA grade was the most frequent with 24%, indicating that the population comes in later stages of the complication when amputation is perhaps the only treatment and hospital management was only to stabilize the metabolic state followed by chemotherapy with scheme combined; to 95% of the patients underwent topical cures were used routinely to prevent recurrence of infection and speed up healing of wounds and the 55% of patients required surgical cleaning; also it revealed that 5 of 10 patients suffered some degree of amputation surgery. Keywords: Diabetic Foot, Risk factors, classification of Wagner, amputation.